2015
DOI: 10.1016/j.jff.2015.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of anthocyanin extract from genotyped Solanum tuberosum L. “Vitelotte”

Abstract: The action of anthocyanins contained in the Vitelotte potato (Solanum tuberosum L.) in both breast and haematological cancers were investigated. The biomedical activities of anthocyanin extract derived from the Vitelotte cultivar were determined. Molecular genotyping was performed to properly identify this outstanding genotype in comparison to other potato varieties and to promote the utilization of this genetic resource by plant breeders. Furthermore, cellular and molecular characterization of the action of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 28 publications
3
35
0
4
Order By: Relevance
“…The observation suggests that anthocyanin-enriched sweet potato P40 has a protective effect against colorectal cancer by inducing cell-cycle arrest, anti-proliferative, and through apoptotic mechanisms. Another study also proves that anthocyanin extract (2 and 5 mg/ml) of purple potato induces maturation of acute myeloid leukemia cells via TNF-related apoptosis-inducing ligand [84]. Moreover, the less common anthocyanin source from vine was reported having anti-invasive property in human hepatoma Hep3B cells in a cancer study [83].…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 97%
“…The observation suggests that anthocyanin-enriched sweet potato P40 has a protective effect against colorectal cancer by inducing cell-cycle arrest, anti-proliferative, and through apoptotic mechanisms. Another study also proves that anthocyanin extract (2 and 5 mg/ml) of purple potato induces maturation of acute myeloid leukemia cells via TNF-related apoptosis-inducing ligand [84]. Moreover, the less common anthocyanin source from vine was reported having anti-invasive property in human hepatoma Hep3B cells in a cancer study [83].…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 97%
“…Particularly attractive are purple-fleshed potatoes, in that they contain higher amount of phenolics as compared to white-fleshed ones [5]. The color of pigmented varieties is due to the presence of additional specific phenolic molecules, called anthocyanins [6][7][8]. In nature, anthocyanins provide pigmentation to different plant organs (flowers, fruits, leaves, and seeds), and are particularly abundant in black or blue colored fruits and vegetables, as well as in their derivatives (e.g., red wines).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, given the many interesting biological activities, pigmented foods have a huge potential for the extraction of natural colorants and antioxidants, which are useful for developing new nutraceuticals [11]. Many in vitro studies have revealed the potential beneficial health effects of pigmented tuber extracts [3,6,7]. Pigmented potatoes display two to three times higher antioxidant potential than white-fleshed potato, and a synergic effect of the mixture of anthocyanins and other antioxidants contained in potato tubers has been demonstrated [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Common polyphenolic compounds mainly include flavones, anthocyanins, phenolic acids, and flavan‐3‐ols. Among these compounds, anthocyanins have attracted the attention of researchers because they are important plant pigments, pollinator attractants, and confer pathogen resistance, among other bioactivities (Bontempo et al, ; Dongyeok et al, ). Fruits rich in anthocyanins have been shown to have superior antioxidative and antiproliferative function (Gan et al, ; Mazewski, Liang, & Gonzalez, ; Święciło et al, ; Veljković et al, ).…”
Section: Introductionmentioning
confidence: 99%